Effects of β-Blockers on the Sympathetic and Cytokines Storms in Covid-19 - Al-kuraishy, Hayder M.; Al-Gareeb, Ali Ismail; Mostafa-Hedeab, Gomaa; Kasozi, Keneth Iceland; Zirintunda, Gerald; Aslam, Akhmed; Allahyani, Mamdouh; Welburn, Susan Christina; Batiha, Gaber El-Saber (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a causative virus in the development of coronavirus disease 2019 (Covid-19) pandemic. Respiratory manifestations of SARS-CoV-2 infection such as acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) lead to hypoxia, oxidative stress, and sympatho-activation and in severe cases lead to sympathetic storm (SS). On the other hand, exaggerated immune response to the SARS-CoV-2 invasion may lead to uncontrolled release of pro-inflammatory cytokine development of cytokine storm (CS). In Covid-19, there are interactive interactions between CS and SS in the development of multi-organ failure (MOF). Interestingly, cutting the bridge between CS and SS by anti-inflammatory and anti-adrenergic agents may mitigate complications that are induced by SARS-CoV-2 infection in severely affected Covid-19 patients. The potential mechanisms of SS in Covid-19 are through different pathways such as hypoxia, which activate the central sympathetic center through carotid bodies chemosensory input and induced pro-inflammatory cytokines, which cross the blood-brain barrier and activate sympathetic center. β2-receptors signaling pathway play a crucial role in the production of pro-inflammatory cytokines, macrophage activation, and B-cells for the production of antibodies with inflammation exacerbation. β-blockers have anti-inflammatory effects through reduction release of pro-inflammatory cytokines with inhibition of NF-κB. In conclusion, β-blockers interrupt this interaction through inhibition of several mediators of CS and SS with prevention development of neural-cytokine loop in SARS-CoV-2 infection. Evidence from this study triggers an idea for future prospective studies to confirm the potential role of β-blockers in the management of Covid-19.